Seroprevalence and placental transmission of maternal antibodies specific for Neisseria meningitidis Serogroups A, C, Y and W135 and influence of maternal antibodies on the immune response to a primary course of MenACWY-CRM vaccine in the United Kingdom. - Blanchard-Rohner, G; Snape, MD; Kelly, D; O'Connor, D; John, T; Kibwana, E; Parks, H; Ford, K; Dull, P; Pollard, A (2013)
BACKGROUND: Maternal antibodies give neonates some protection against bacterial infection. We measured antibodies against Neisseria meningitidis serogroups A, C, Y and W135 in mothers and their 2-month-old infants at study enrollment. We also assessed the impact of maternal antibody present at 2 months of age on the immune response to a primary course of quadrivalent meningococcal conjugate vaccine (MenACWY-CRM197) given at 2 and 4 months of age. METHODS: This was a single-center, open-label, randomized study undertaken in Oxford, United Kingdom. Two hundred sixteen healthy infants were enrolled in the study and vaccinated with MenACWY-CRM197 at 2 and 4 months of age. Blood was obtained from all mothers, in a subset of infants at 2 months and all infants at 5 months. Antibody and memory B-cell responses at 5 months were correlated with maternal antibodies. RESULTS: Mothers had low IgG antibodies against serogroups C, W135 and Y polysaccharides, but high serogroup A antibody, whereas 61-78% had protective human complement serum bactericidal activity (hSBA) (≥1:4) for serogroups C, W135 and Y but only 31% for serogroup A. Only 9%, 32%, 45% and 19% of 2-month-old infants had hSBA ≥1:4 for serogroups A, C, W135 and Y, respectively. Maternal antibody had little association on responses to MenACWY-CRM197, except a moderate negative association between MenC-specific bactericidal antibody at 2 and 5 months (r = -0.5, P = 0.006, n = 28) and between carrier-specific IgG antibody at 2 months and MenC-specific hSBA/IgG antibody at 5 months (r = -0.4, P = 0.02 and 0.04, n = 32 and 23). Nonetheless, 90% of infants achieved protective MenC-hSBA titers after vaccination at 2 and 4 months of age. CONCLUSIONS: The levels of serogroup-specific meningococcal antibodies were low in mothers and 2-month-old infants. Immunizing mothers before or during pregnancy with meningococcal conjugate vaccines might increase antibody levels in early infancy and provide protection against infection due to N. meningitidis.